POTENSI PENDIRIAN BANK WAKAF MIKRO SEBAGAI SARANA PENGUATAN EKONOMI UMAT ISLAM (STUDI KASUS PESANTREN DI KABUPATEN MANDAILING NATAL) - Vebri Sugiharto (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The government's implementation of strengthening the Islamic economy has received recognition from the community. The government's goal is to carry out the economic strengthening so that the people are freed from the economic hardships amid the Covid-19 that is plaguing Muslims today. Efforts to strengthen the Islamic economy by encouraging the establishment of small capital banks operating in Islamic boarding schools. The presence of the Small Waqf Bank (BWM) is expected to be able to facilitate the economy of the community around the pesantren environment. The presence of a small endowment bank in Islamic boarding schools in the Mandailing Natal Regency aims to facilitate the financing of the Mandailing Natal community. The aim of this study is to provide an overview, organization and mechanism of the work of small capital banks to facilitate the economy of Muslims in Islamic boarding schools. Thus, this research uses qualitative research with the descriptive type. The results of this study point to the possibility of establishing a small endowment bank in the pesantren environment of the Mandailing Natal Regency.